2021
DOI: 10.24115/s2446-6220202172749p.364-384
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pandemic process on special education in Cyprus

Abstract: In this paper, the education programs offered to students with special needs in the online distance education format during the Covid-19 pandemic period in TRNC and the online family guidance/counseling services offered to their families were evaluated from the perspective of the families.  In the study, the data obtained follow a parallel course with other studies in the literature. In studies on the academic support provided by families for children and family participation in learning processes, the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 13 publications
3
5
0
Order By: Relevance
“…Online learning was also inseparable from the constraints of an inadequate internet network in the student's home area due to the geographical conditions of learners' homes which were sometimes difficult to reach by the internet network. It was in line with previous research by Ariesca et al (2021), Putria et al (2020), andGökbulut et al (2021) that learners experienced internet network problems in the implementation of online learning. The teacher also felt the constraints of the internet network.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Online learning was also inseparable from the constraints of an inadequate internet network in the student's home area due to the geographical conditions of learners' homes which were sometimes difficult to reach by the internet network. It was in line with previous research by Ariesca et al (2021), Putria et al (2020), andGökbulut et al (2021) that learners experienced internet network problems in the implementation of online learning. The teacher also felt the constraints of the internet network.…”
Section: Discussionsupporting
confidence: 92%
“…Slow learners were getting bored and bored in participating in online learning. This condition was in line with research conducted by Wahyuningtyas and Sulasmono (2020), Putria et al (2020), andGökbulut et al (2021). The condition of learners who felt bored and bored with online learning could cause learners with special needs to experience tantrums (Prasetyo & Supena, 2021).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“… 19 The results of the studies in the literature showed parallelism with our study and showed that children with disabilities had difficulties in getting education during the pandemic process, could not benefit from distance education and mothers were not enough to provide education. 17 , 18 , 20 , 31 , 33 , 47 - 49 However, in some studies, it has been stated that mothers do not know how to get their children to do activities and it is important for mothers to be educated on this issue. 50 - 53 Another problem is that children with disabilities cannot benefit from distance education due to social inequalities, and there are studies supporting this result.…”
Section: Discussionmentioning
confidence: 99%
“…While it is important for children with disabilities to receive support from a specialist at home during the pandemic process, it has been reported that children cannot receive support from a specialist at home, similar to our study. 20 , 47 , 48 , 55 …”
Section: Discussionmentioning
confidence: 99%